Juridical Analysis: Digital Identity of Children from Stelse International Mixed Marriages - Septia Nugraha, Dirga; Hermiati Nurmilan, Siti (KnE Social Sciences, 2024)
The importance of having self-identity by every individual is a necessity, including the identity of a newborn child. Identity is the right of every citizen, and the state has an obligation to carry out services, procurement, and spending as part of the legitimacy and legality of identity owned by each citizen. Developments in technology, modernization, and globalization, as well as the era of digitalization, can encourage and assist the process of having a digital self-identity of children from birth. This will be very influential in reducing acts of exploitation, such as trafficking, violence, exile, neglect, and other criminal acts. Therefore, the researcher takes a legal analysis approach to all applicable regulations in Indonesia related to access policies, and processes to disclosure of children’s identities. The results of the analysis carried out included, among other things, the enforcement of the provisions of the 1945 Constitution Article 28, Law Number 12 of 2006 concerning Citizenship, Law Number 23 of 2006 Population Administration, and Law Number 23 of 2014 concerning the ratification of Child Protection can become a legal umbrella for child ownership. In addition, the identity ownership of children from mixed marriages will be influenced by the validity of the marriage of their parents or the application for legalization through consanguine marriage in accordance with Law No. 1 of 1974. The process of owning a child’s digital identity will involve 3 institutions and or related agencies, including hospitals or maternity clinics as agencies that issue birth certificates, the Ministry of Religion as an institution that issues legal marriage certificates, and the Ministry of Home Affairs that issues valid personal identities in the form of temporary E-KTP and immigration passports. Keywords: digital identity, birth certificate, mixed marriage